Assessing classroom environment and attitude of technical students towards mathematics and the association between them - Khalid, Madihah (Common Ground Publishing, 2007)
The use of students' and teachers' perception of their educational environments can assist educators determine the preference of each group in teaching and learning and thus assist in improving the environment. This would hopefully result in more effective teaching and learning conditions that can thus improve students' achievement. Studying students' attitudes towards learning is also beneficial and can be used to improve their achievement levels as well. In this study that involves 239 technical students in Brunei Darussalam, a Classroom Environment Survey and an Attitude towards Mathematics Survey was developed and administered. The classroom environment survey consists of 56 items with 8 scales, each scale being assessed by 7 items, while the attitude survey consists of 20 items with 5 items assessing 4 different scales. The quantitative data from this survey and the qualitative data from interviews of teachers and students were analysed and the outcomes of the analyses were used in determining the actual environment and students' preferences. These results were used to assist in the design of a suitable instructional model for the development of a teaching and learning package. This paper considers the development of the survey questionnaire and the outcomes of the analyses. The association between classroom environment and attitude is also examined and presented. At the conclusion of the paper a number of recommendations for a better classroom are discussed.